1980
DOI: 10.1038/bjc.1980.43
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin shortens the half-life of the hypoxic cell radiosensitizer misonidazole in man: implications for possible reduced toxicity

Abstract: Previous studies from this laboratory have shown that pretreatment with phenytoin or phenobarbitone shortens the halflife of MISO in mice and dogs through induction of hepatic drug-metabolizing enzymes, which increase the rate of oxidative demethylation of MISO to desmethylmisonidazole (1-(2-nitroimidazol-1 -yl)-2,3-propandiol; Ro 05-9963, Roche Laboratories; NSC 261036; DEMIS) (Workman, 1979; White & Workman, 1979). In addition, pretreatment with these agents significantly reduces the acute lethal effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…We believe that this is the result of two separate phenomena. We have shown that anticonvulsant therapy with phenytoin (Workman et al, 1980) and phenobarbitone (unpublished) reduce the plasma half-life of MISO because of hepatic microsomal-enzyme induction. The t-of 8-6 h + 0-62 observed in this study, compared to 11*5 h + 3 8 in our experience of patients without brain tumours, suggests that increased drug metabolism may be reducing the peripheral-nerve exposure to MISO.…”
Section: Resultsmentioning
confidence: 95%
“…We believe that this is the result of two separate phenomena. We have shown that anticonvulsant therapy with phenytoin (Workman et al, 1980) and phenobarbitone (unpublished) reduce the plasma half-life of MISO because of hepatic microsomal-enzyme induction. The t-of 8-6 h + 0-62 observed in this study, compared to 11*5 h + 3 8 in our experience of patients without brain tumours, suggests that increased drug metabolism may be reducing the peripheral-nerve exposure to MISO.…”
Section: Resultsmentioning
confidence: 95%
“…The major dose-limiting toxicity of MISO remains its neurotoxicity, for which the concomitant use of phenytoin has been suggested as a means of reducing this effect (Wasserman et al, 1980;Workman et al, 1980). This study has demonstrated the time-course of the phenytoin-induced change in the pharmacokinetics of MISO in patients receiving radical radiotherapy, and it has shown that the half-life of both T-NITRO and MISO are significantly reduced by it.…”
mentioning
confidence: 76%
“…Studies in this laboratory and elsewhere have shown that the rate of metabolism of misonidazole can be influenced by other drugs such as phenytoin and phenobarbitone (Williams et al, 1983;Workman et al, 1980). Induction of metabolism may reduce the neurotoxicity of misonidazole by decreasing tissue exposure to the drug.…”
Section: No Significant Effect Of Cimetidine On the Pharmacokinetics mentioning
confidence: 88%